Islamic Social Welfare in DK Jakarta: Addressing Inequality and Promoting Social Cohesion - Luhuringbudi, Teguh; Putra, Purnama; Utami, Dewi Nita (Pusat Pengkajian dan Pengembangan Islam Jakarta (PPIJ), 2024)
This research paper examines the role of Islamic social welfare in addressing inequality and enhancing social cohesion in Daerah Khusus Jakarta (DKJ). Using a descriptive qualitative approach, this study analyzes official statistical data from DK Jakarta in 2022-2024 through the theoretical framework of Putnam's social capital, Crenshaw's intersectionality, and Foster-Iaione's urban commons. Key findings reveal the effectiveness of the zakat-waqf network in mitigating the impact of inflation, reducing it from 3.30% (2022) to 1.98% (2024). Mosques act as centers of socio-economic innovation through programs such as